Effect of the gibberellic acid and benzilaminopurine on the in vitro growth of embryos of coffee plants cv. Acaiá - Rodrigues Carvalho, Gladyston; Pasqual, Moacir; José Guimarães, Rubens; Nazareno Guimarães Mendes, Antônio; Eduardo Corrêa Antunes, Luis; Tadeu da Silva, Antônio (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this work was to evaluate the effect of different concentrations of gibberellic acid (GA3) and citokinin on the in vitro growth of embryos of the coffee (Coffea arabica L.) plant cv. Acaiá. The experiment was done in the tissue culture laboratory of the Universidade Federal de Lavras (Federal University of Lavras). The experimental design used was in random blocks in 4 x 4 factorial scheme with four tubes per parcel and one embryo per tube. The treatments consisted of different concentrations of GA3 (0, 2, 4 and 8 mg/L) and benzilaminopurine (BAP) (0, 2, 4, and8 mg/L). The culture medium used was solidified MS with 7 g/L of agar and pH adjusted to 6.1 before autoclaving. The results showed that the increase of GA3 concentration reduces rooting and the BAP does not influence this process. The citokinin BAP is dispensable for the culture of the coffee plant embryos, while GA3 contributes to their development.